2005
DOI: 10.1111/j.1600-051x.2005.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to utilization of dental services during pregnancy

Abstract: There was limited knowledge of the possible relationships between oral health and pregnancy outcomes in a fairly homogeneous population of women who were of relatively high socioeconomic standing. This study suggests that better education of the importance of dental care before and during pregnancy is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
131
6
19

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(181 citation statements)
references
References 23 publications
(42 reference statements)
21
131
6
19
Order By: Relevance
“…Similar results were seen in the study conducted by Thomas et al 4 in which, although 91% of pregnant women stated they brushed their teeth one or more times a day, around 30% attended the dentist while pregnant. This result was also substantiated by Hajikazemi et al, 1 Bamanikar and Kee, 14 and Al Habashneh et al 15 in their study. Practice of pregnant women belonging to low socioeconomic group was not good, which might be because of poor knowledge toward oral health, unaffordability of dental treatment, and cultural misbelieves.…”
Section: Discussionsupporting
confidence: 79%
“…Similar results were seen in the study conducted by Thomas et al 4 in which, although 91% of pregnant women stated they brushed their teeth one or more times a day, around 30% attended the dentist while pregnant. This result was also substantiated by Hajikazemi et al, 1 Bamanikar and Kee, 14 and Al Habashneh et al 15 in their study. Practice of pregnant women belonging to low socioeconomic group was not good, which might be because of poor knowledge toward oral health, unaffordability of dental treatment, and cultural misbelieves.…”
Section: Discussionsupporting
confidence: 79%
“…T here is a widely held belief among women that childbearing is related to oral disease (Habashneh et al, 2005;Payscale.com, 2007;Yahoo, 2010). Indeed, several studies over the last decade have shown that parity (number of children) is related to tooth loss (Rundgren and Osterberg, 1987;Halling and Bengtsson, 1989;Christensen et al, 1998;, but the reason for this relationship is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Evidências científicas mostram que as mudanças fisiológicas geradas pela gestação podem repercutir na homeostase da cavidade bucal devido, principalmente, a variações hormonais que produzem alterações na resposta imunológica da gestante (6) . Estudos indicam que inflamação crônica dos tecidos de sustentação dos dentes, focos de infecção, dor e possibilidade de septicemia, durante a gestação, possam ser fatores de risco à parto prematuro, recém-nascido com baixo peso, pré-eclampsia e aborto (7,9) . O objetivo deste estudo foi conhecer as percepções do enfermeiro que atua na estratégia de saúde da família sobre a organização da atenção a saúde bucal prestada à mulher gestante.…”
Section: Introductionunclassified